Patient priorities for research: A focus group study of UK medical cannabis patients. (February 2023) - Erridge, Simon; Olsson, Fabian; Sodergren, Mikael H.
Abstract: Introduction: There has yet to be an evaluation of medical cannabis patient preferences with respect to future research. As such, prioritisation of research agendas has been largely driven by academia and industry. The primary aim of this study was to elicit priorities for research from medical cannabis patients in the United Kingdom (UK). Methods: Patients undergoing active treatment for health conditions with medical cannabis in the UK were invited to take part in focus groups from December 2021 to February 2022. An inductive thematic analysis of responses was performed. Participants also completed a ranking exercise whereby they assigned ten counters (each equivalent to £1 million GBP) to competing research priorities. Results: 30 medical cannabis patients participated across 3 focus groups. The following themes were identified as research priorities: adverse events, comparison between cannabis-based medicinal products, health conditions, pharmacology of cannabis, types of study, healthcare professionals' attitudes, social environment, agriculture and manufacturing, and the cannabis plant. Participants assigned the highest proportion of research funding to 'assessment of effect on specific symptoms' (26 counters; 8.7%). Conclusions: This study highlighted specific themes within which to focus future research on medical cannabis. Clinically, there was a directive towards ensuring that research is condition- or symptom-specific. Participants also emphasised themes on the social impact of medical cannabis, such as knowledge of medical cannabis among healthcare professionals, stigma, and effects on driving and in the workplace. These findings can guide both research funders and researchers into effectively conducting research which fits within a more patient-centric model. Highlights: Three research domains were identified: Clinical, Barriers, and Development. Medical cannabis patients prioritise condition- or symptom-specific research. The social impact of medical cannabis is also an important research priority.